2022
DOI: 10.1590/0001-3765202220211283
|View full text |Cite
|
Sign up to set email alerts
|

Does being infected with SARS-CoV-2 in the first-trimester increase the risk of miscarriage?

Abstract: Aim of this study is to investigate whether the risk of miscarriage increases in pregnant women who had COVID-19 in fi rst trimester. Our study included 52 patients with SARS-CoV-2 infection detected by RT-PCR and 53 patients with negative RT-PCR test in samples taken with nasopharyngeal swab in the fi rst trimester between March 1 and December 31, 2020. Complete abortion, incomplete abortion, blighted ovum, intrauterine exitus, biochemical pregnancies were accepted as in the miscarriage group (MG). Pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…included women infected before gestational week 20. 20 , 22 Eleven articles focused on maternal and obstetric outcomes, 2 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 whereas seven focused on neonatal outcomes only. 16 , 20 , 21 , 22 , 32 , 33 , 34 For the diagnosis of SARS‐CoV‐2 infection, all but six studies relied exclusively on clinically confirmed reverse transcription polymerase chain reaction, whereas two relied on self‐reported data on infection and four studies also included pregnant women with positive antibody serology (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…included women infected before gestational week 20. 20 , 22 Eleven articles focused on maternal and obstetric outcomes, 2 , 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 whereas seven focused on neonatal outcomes only. 16 , 20 , 21 , 22 , 32 , 33 , 34 For the diagnosis of SARS‐CoV‐2 infection, all but six studies relied exclusively on clinically confirmed reverse transcription polymerase chain reaction, whereas two relied on self‐reported data on infection and four studies also included pregnant women with positive antibody serology (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 studies included in this review, 12 were retrospective, including 10 cohort studies and two case-control studies, and six were prospective cohort studies, including a total of 10 147 COVID- fore gestational week 20. 20,22 Eleven articles focused on maternal and obstetric outcomes, 2,19,[23][24][25][26][27][28][29][30][31] whereas seven focused on neonatal outcomes only. 16,[20][21][22][32][33][34] For the diagnosis of SARS-CoV-2 infection, all but six studies relied exclusively on clinically confirmed reverse transcription polymerase chain reaction, whereas two relied on self-reported data on infection and four studies also included pregnant women with positive antibody serology (Table 1).…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%